On Sand and the Role of Grease in Labor Markets : How Does Germany Compare? - Decressin, Jorg (IMF Working Papers; Working Paper, 2002)
This paper investigates wage setting in (west) Germany using the German Socioeconomic Panel dataset on individuals and compares the findings with those available for the United Kingdom and the United States. The fraction of job stayers in (west) Germany who suffer unchanged wages or wage cuts compares with that in similar data for the Anglo-American countries, even after various adjustments for potential reporting errors. While nominal wages of job stayers are rigid downward, real wages are not. Nevertheless, the macroeconomic effects of the nominal rigidity are limited and cannot be weakened substantially by raising inflation.